Physiological and metabolic profiles of common reed provide insights into plant adaptation to low nitrogen conditions. (August 2017) - Chu, Xiaodan; Yang, Lan; Wang, Shuang; Liu, Jun; Yang, Haijun
Abstract: One of the most distinct features of the common reed ( Phragmites australis ) is its ability to survive under extremely low nitrogen conditions. To explore the regulation mechanisms of reed to adapt to nitrogen deficiency, we treated reed seedlings under long-term extremely low nitrogen conditions and profiled the physiological and metabolic features of photosynthesis, metabolism, growth, nutrient balance, and enzyme activities. Unexpectedly, the photosynthesis, biomass and carbon content were still maintained at high levels in reed under N-deficient conditions regardless of the decreased content of chlorophyll and nitrogenous compounds. Using mass spectrometry, we profiled metabolism of 627 metabolites and found the concentrations of lactic acid and galactinol were accumulated under the treatment. The development of underground organs and nutrient accumulation (B, P, Zn and Na) were also enhanced under the condition. Unlike the positive correlation of nitrate reductases and N levels in other plants, we found the catalytic activities of nitrate reductases were dramatically elevated in roots under the N-deficient condition, which may increase the intracellular NO3 − and NH4 + levels. Our experiments characterized the unique features of reed under extreme nitrogen deficiency conditions and also provided valuable information for other corps to develop the cultivars with high yield under low nitrogen input.